Birth seasons and heights among girls and boys below 12 years of age: lasting effects and catch-up growth among native Amazonians in Bolivia. (19th May 2018) - Brabec, Marek; Behrman, Jere R; Emmett, Susan D.; Gibson, Edward; Kidd, Celeste; Leonard, William; Penny, Mary E.; Piantadosi, Steven T.; Sharma, Abhishek; Tanner, Susan; Undurraga, Eduardo A.; Godoy, Ricardo A
Abstract: Background: Seasons affect many social, economic, and biological outcomes, particularly in low-resource settings, and some studies suggest that birth season affects child growth. Aim: To study a predictor of stunting that has received limited attention: birth season. Subjects and methods: This study uses cross-sectional data collected during 2008 in a low-resource society of horticulturists-foragers in the Bolivian Amazon, Tsimane'. It estimates the associations between birth months and height-for-age Z -scores (HAZ) for 562 girls and 546 boys separately, from birth until age 11 years or pre-puberty, which in this society occurs ∼13–14 years. Results: Children born during the rainy season (February–May) were shorter, while children born during the end of the dry season and the start of the rainy season (August–November) were taller, both compared with their age–sex peers born during the rest of the year. The correlations of birth season with HAZ were stronger for boys than for girls. Controlling for birth season, there is some evidence of eventual partial catch-up growth, with the HAZ of girls or boys worsening until ∼ age 4–5 years, but improving thereafter. By age 6 years, many girls and boys had ceased to be stunted, irrespective of birth season. Conclusion: The results suggest that redressing stunting will require attention to conditions in utero, infancy and late childhood.